2007
DOI: 10.1187/cbe.07-06-0039
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Research Experiences Support Science Career Decisions and Active Learning

Abstract: The present study examined the reliability of student evaluations of summer undergraduate research experiences using the SURE (Survey of Undergraduate Research Experiences) and a follow-up survey disseminated 9 mo later. The survey further examines the hypothesis that undergraduate research enhances the educational experience of science undergraduates, attracts and retains talented students to careers in science, and acts as a pathway for minority students into science careers. Undergraduates participated in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
815
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 802 publications
(855 citation statements)
references
References 13 publications
32
815
0
8
Order By: Relevance
“…First, students have the opportunity to make relevant findings that could be continued in the context of a research project. The importance of undergraduate research in student learning has been shown many times [18][19][20]. While this class is not an independent research experience, students can use the findings gained in the course as a springboard for a more in-depth independent research project.…”
Section: Course Adaptability and Alternativesmentioning
confidence: 99%
“…First, students have the opportunity to make relevant findings that could be continued in the context of a research project. The importance of undergraduate research in student learning has been shown many times [18][19][20]. While this class is not an independent research experience, students can use the findings gained in the course as a springboard for a more in-depth independent research project.…”
Section: Course Adaptability and Alternativesmentioning
confidence: 99%
“…For example, it is important to consider what resources (personnel, reagents, space) can be devoted to a CURE, how the research project can be organized into discrete units of time, how potentially hundreds of students can work on a project that offers both enough similarities to provide a common curriculum and differences to give students a sense of project ownership, and how instructional guidance can ensure that students are thinking and learning, rather than simply “going through the motions.” Doing this at scale is particularly challenging. Yet, despite these challenges, studies indicate that both types of experiences improve students′ ability to engage in scientific practices and their desire to pursue additional research opportunities (e.g., 9, 10, 11, 12, 13). These findings have prompted national calls for implementation of CUREs at the introductory level 2.…”
Section: Introductionmentioning
confidence: 99%
“…Much is written about undergraduate research students' experience(s) in the natural sciences or science, technology, engineering and maths (STEM) subjects (see, e.g., Linn et al [2015]; Thiry and Laursen [2011]; Balster et al [2010]; Lopatto [2010Lopatto [ , 2007Lopatto [ , 2004; Shellito et al [2001] and Sabatini [1997]). However there are fewer discussions around undergraduate research where contexts and datasets span, or compare, the natural and social sciences (see, e.g., Jenkins [2009a, 2009b]; Taylor and Wilding [2009]; Russell, Hancock and McCullough [2007]; Kinkead [2003]; Hathaway, Nagda and Gregerman [2002]) and far fewer examples that focus solely on the social sciences (see, e.g., Kilburn, Nind and Wiles [2014]; Todd, Bannister and Clegg [2004]; Ishiyama [2002]).…”
Section: Literature Reviewmentioning
confidence: 99%